2018
DOI: 10.1038/s41467-018-06830-w
|View full text |Cite
|
Sign up to set email alerts
|

Defluorosilylation of fluoroarenes and fluoroalkanes

Abstract: Direct activation of carbon–fluorine bonds (C–F) to introduce the silyl or boryl groups and generate valuable carbon–silicon (C–Si) or carbon–boron (C–B) bonds is important in the development of synthetically useful reactions, owing to the unique opportunities for further derivatization to achieve more complex molecules. Despite considerable progress of C–F bond activation to construct carbon–carbon (C–C) and carbon–heteroatom (C–X) bond formation, the defluorosilylation via C–F cleavage has been rarely demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(78 citation statements)
references
References 40 publications
2
75
0
1
Order By: Relevance
“…It has been reported that R 3 Si−B(pin) can efficiently form a silyl‐borate complex with alkoxides, but it was not clear whether a highly reactive silyl anion equivalent could be generated from the silyl‐borate species and practically utilized. We selected the defluorosilylation reaction of Ph−F as a model reaction, based on the experimental observation by Würthwein and Studer that the S N Ar (nucleophilic aromatic substitution) reaction of unactivated fluoroarenes with silyllithiums proceeds smoothly without any transition metal (TM) catalyst . S N Ar reaction has long been considered to proceed in a stepwise manner via the Meisenheimer intermediate, though more recently an in‐depth mechanistic study by Jacobsen demonstrated that S N Ar reaction also occurs via a concerted pathway…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that R 3 Si−B(pin) can efficiently form a silyl‐borate complex with alkoxides, but it was not clear whether a highly reactive silyl anion equivalent could be generated from the silyl‐borate species and practically utilized. We selected the defluorosilylation reaction of Ph−F as a model reaction, based on the experimental observation by Würthwein and Studer that the S N Ar (nucleophilic aromatic substitution) reaction of unactivated fluoroarenes with silyllithiums proceeds smoothly without any transition metal (TM) catalyst . S N Ar reaction has long been considered to proceed in a stepwise manner via the Meisenheimer intermediate, though more recently an in‐depth mechanistic study by Jacobsen demonstrated that S N Ar reaction also occurs via a concerted pathway…”
Section: Methodsmentioning
confidence: 99%
“…[35,36] This phenomenon also indicated the reason why off-target bindings frequently occurred in dSpCas9. [37] However, the extent of the heteroduplex toward the PAM-distal region determines the activity of DNA cleavage. [35,36,38] Upon the occurrence of the DNA binding event, a simultaneous movement of the HNH domain is triggered, bringing the HNH domain to the scissile phosphate site on the target DNA strand.…”
Section: Wwwadvancedsciencenewscom Wwwsmall-methodscommentioning
confidence: 99%
“…Comparing to the construction of the single-gene knockout library in bacteria, building a CRISPR-dCas9 based single-gene knockdown library costs much less labor, time, and budget (Table S2, Supporting Information). [37,[188][189][190] For instance, the essential genes in S. pneumoniae have been identified from previous transposon sequencing (Tn-seq) works. [189] However, the insertion of a transposon into an essential gene leads to cell death.…”
Section: Constructing Gene Knockdown Librarymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inherent problems such as ambiguous interpretation of CRISPRi results when targeting a bidirectional promoter or upstream versus downstream genes in operons exist [135,136] and require caution and further experimentation for full comprehension. Several studies reported dCas9 protein off-target effect, besides toxicity in bacterial cells [137][138][139][140][141][142]. In E. coli, it was observed that a high level of dCas9 expression led to abnormal cell morphology [137].…”
Section: Limitations Of Crispri and Future Directionsmentioning
confidence: 99%